ANALISIS EFEKTIVITAS KAWASAN BERNILAI KONSERVASI TINGGI SEBAGAI HABITAT SATWA LIAR DI PERKEBUNAN KELAPA SAWIT PT BUMI PERMAI LESTARI - Lubis, Habib Twindy; Dalimunthe, Nurzaidah Putri; Syafutra, Randi (Innovative: Journal Of Social Science Research, 2025)
This research focuses on the High Conservation Value (HCV) area within the concession of PT Bumi Permai Lestari (PT BPL), a palm oil plantation company operating in West Bangka Regency, Bangka Belitung Islands Province. This study aims to assess the function of the High Conservation Value (HCV) from a biodiversity perspective and can serve as a reference for improving the management of the area in the future. Wildlife Inventory: Conducted through two main methods, namely Direct Observation/recce walk along 500-1000 meters within the area designated as the primary HCV observation route in the morning, afternoon, and evening. Observation of traces and signs of animal presence such as recording footprints, droppings, sounds, or traces of animal food. Based on the analysis, it was concluded that the biodiversity of mammalian species is in the low category. Meanwhile, the aves species are in the medium category with a value of 1 and herpetofauna are in the medium diversity category, Aves with 1.90 and herpetofauna are in the low class with 0.79 points.